Laboratory Diagnostics of Antiphospholipid Syndrome - Pengo, Vittorio; Bison, Elisa; Denas, Gentian; Jose, Seena Padayattil; Zoppellaro, Giacomo; Banzato, Alessandra (Seminars in Thrombosis and Hemostasis, 2018)
Diagnosis of antiphospholipid syndrome (APS) lies in the recognition of antiphospholipid antibodies (aPL). As standardization of tests for the detection of aPL is far from being optimal and reference material is not available, inappropriate diagnoses of APS are not unusual. In the last few years, the concept of triple test positivity has emerged as a useful tool to identify patients with APS. Clinical studies on patients and carriers of triple positivity clearly show that these individuals are at high risk of thromboembolic events and pregnancy loss. Moreover, triple positivity arises from a single (probably pathogenic) antibody directed to domain 1 of β2-glycoprotein I, a protein whose function is still unknown. Studies on homogenous group of patients with single or double positivity are scant, and uncertainties arise on their association with clinical events. Promising but undetermined results come also from the determination of antibodies directed to phosphatidylserine/prothrombin complex. Interpretation of laboratory profile in APS is challenging, and the collaboration between clinical pathologists and clinicians is highly desirable.
Keywords: cardiolipin; β2-glycoprotein I; antibodies; lupus anticoagulant; thrombosis